High-barrier biaxially oriented polyamide film and preparation method thereof
By introducing supramolecular ion polymers into MXD6 and PA6 to peel off nanomontmorillonite and layered double hydroxides, forming a three-layer structure high-barrier bidirectional tensile polyamide film, the problem of insufficient barrier performance of existing films is solved. It realizes effective barriers to gas and water vapor, and is suitable for packaging materials for electronic components.
Patent Information
- Application Number
- CN202310856941.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-13
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-07-13
AI Technical Summary
The barrier properties of existing bidirectional tensile polyamide films are not sufficient to meet the packaging requirements of electronic components, especially in high humidity conditions, which cannot effectively block gas and water vapor.
Using multi-layer composite and nanocomposite combination method, a high-barrier bidirectional stretched polyamide film was prepared. By introducing supramolecular ion polymer into MXD6 and PA6, a three-layer structure was formed. The film, where the A and C layers are composed of PA6, MXD6 and high barrier masterbatch, and the B layer is composed of MXD6 and PA6, and is subjected to corona treatment to improve the barrier performance of the film.
It significantly improves the gas and water vapor barrier properties of the film, extends the gas permeability path, reduces the gas diffusion rate, and is suitable for packaging materials under high humidity conditions.
Smart Images

Figure CN119305280A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-barrier biaxially stretched polyamide film and a preparation method thereof. Background Art
[0002] Biaxially oriented polyamide 6 (BOPA6) film is the third largest polymer film packaging material after biaxially oriented polypropylene (BOPP) and biaxially oriented polyethylene terephthalate (BOPET). It has a wider operating temperature range (-60 to 150°C), better gas barrier properties, and excellent puncture resistance, wear resistance, solvent resistance and other properties. It is widely used in food and pharmaceutical packaging and other fields. With the rapid development of new energy and microelectronics industries, especially in order to preserve food, medicine, electronic components, military supplies, etc., higher requirements are placed on the barrier properties of packaging materials. Although the barrier properties of BOPA6 film are relatively good, it is not enough to meet the packaging requirements of electronic components.
[0003] In order to improve the barrier properties of BOPA6 film, many methods such as multilayer composite, blending, copolymerization, coating, layer-by-layer self-assembly, vacuum evaporation, nanocomposite, etc. have developed rapidly. At present, the mainstream products in the high barrier film market are polyvinyl alcohol (PVA) coated high barrier film, PVDC high barrier film, EVOH high barrier film, nylon high barrier film and inorganic oxide coated film; in addition, products such as poly (m-phenylene adipamide) (MXD6) film and silicon oxide evaporation film have also received widespread attention in the market in recent years. Among many methods, the combination of multilayer composite and nanocomposite can give play to the advantages of both methods and improve the barrier properties of the film. Multilayer composite refers to the combination of two or more films with different barrier properties through a certain process. In this way, the penetrating molecules have to pass through several layers of film to reach the inside of the package, which is equivalent to extending the permeation path, thereby improving the barrier properties. Nanocomposite materials are nanocomposite materials prepared by intercalation composite method, in-situ polymerization method or sol-gel method using impermeable flaky nanoparticles with a large aspect ratio. The addition of flaky nanoparticles can not only reduce the volume fraction of the polymer matrix in the system to reduce the solubility of the permeating molecules, but also extend the permeation path of the permeating molecules, reduce the diffusion rate of the permeating molecules, and improve the barrier properties. Combining multi-layer composites with nanocomposites can achieve the effect of functional superposition and obtain better barrier properties. At present, layered nanofillers such as montmorillonite (MMT) and layered double hydroxides (LDHs) have become a hot research topic with their unique structure and excellent performance. Therefore, if MXD6 is used as the surface layer for multi-layer composite with PA6, and MMT is introduced into MXD6, the barrier properties of the film material will be greatly improved. Summary of the invention
[0004] In view of the above-mentioned defects of the prior art, an object of the present invention is to provide a supramolecular ionic polymer exfoliated nano-montmorillonite.
[0005] To solve the above problems, the technical solution of the present invention is: a high barrier biaxially oriented polyamide film, which is composed of three layers of co-extruded biaxially oriented polyamide film, A, B, and C, from top to bottom;
[0006] Layer A and layer C are composed of 10wt% to 20wt% PA6, 66wt% to 83.5XD6, 6wt% to 15 high barrier MXD 6 masterbatch, and 0.5wt% to 3wt% anti-sticking masterbatch;
[0007] The B layer is composed of 10wt% to 20wt% of MXD6, 70wt% to 85wt% of PA6, and 2wt% to 8wt% of high barrier PA6 masterbatch.
[0008] Furthermore, the thickness of the high barrier biaxially oriented polyamide film is 12-25 um, the thickness of the A layer and the C layer are both 2-4 um, and at least one side of the A layer and the C layer is corona treated.
[0009] Furthermore, the anti-sticking masterbatch is a modified polyamide masterbatch containing an anti-blocking agent, a lubricant and a dispersant.
[0010] Furthermore, the high barrier MXD6 masterbatch is MXD6 modified by inorganic layered nanoparticles; and the high barrier PA6 masterbatch is PA6 modified by inorganic layered nanoparticles.
[0011] Furthermore, the inorganic layered nanoparticles are a composite of supramolecular ion polymer exfoliated nano-montmorillonite and supramolecular ion polymer exfoliated layered double hydroxide.
[0012] Furthermore, the supramolecular ionic polymer exfoliated nano-montmorillonite is an exfoliated MMT containing supramolecular ionic polymers composed of melamine cations, multifunctional imidazole cations and heteropolyacid anions between the layers.
[0013] Furthermore, the supramolecular ionic polymer exfoliated layered double hydroxide is an exfoliated LDH of supramolecular ionic polymers composed of sulfonic acid anions, diimidazole cations and heteropolyacid anions between the layers.
[0014] Furthermore, the weight ratio of supramolecular ionic polymer exfoliated nano-montmorillonite to supramolecular ionic polymer exfoliated layered double hydroxide is 4 / 1 to 1 / 2, and the total content of supramolecular ionic polymer exfoliated nano-montmorillonite and supramolecular ionic polymer exfoliated layered double hydroxide in the high barrier PA6 masterbatch is 20wt% to 30wt%.
[0015] Furthermore, the weight ratio of supramolecular ionic polymer exfoliated nano-montmorillonite to supramolecular ionic polymer exfoliated layered double hydroxide is 4 / 1 to 1 / 2, and the total content of supramolecular ionic polymer exfoliated nano-montmorillonite and supramolecular ionic polymer exfoliated layered double hydroxide in the high barrier MXD6 masterbatch is 30wt% to 40wt%.
[0016] The present invention also provides a method for preparing the high barrier biaxially oriented polyamide film, which is characterized by comprising the following steps:
[0017] (1) Preparation of high barrier MXD6 masterbatch:
[0018] Supramolecular ion polymer exfoliated nano-montmorillonite, supramolecular ion polymer exfoliated layered double hydroxide, MXD6, antioxidant, and hyperbranched rheological additive are mixed in proportion, added into a kneader, and stirred evenly to obtain a coarse material;
[0019] The coarse material is crushed and mixed with the coupling agent, and then melt-extruded and granulated by a twin-screw extruder to obtain a masterbatch product. The extruder temperature is set at 250-290°C and the extruder speed is 300r / min-500r / min.
[0020] min, dehumidify and dry, and set aside;
[0021] (2) Preparation of high barrier PA6 masterbatch:
[0022] Supramolecular ion polymer exfoliated nano-montmorillonite, supramolecular ion polymer exfoliated layered double hydroxide, PA6, antioxidant, and hyperbranched rheological additive are mixed in proportion, added into a kneader, and stirred evenly to obtain a coarse material;
[0023] The coarse material is crushed and mixed with the coupling agent, and then melt-extruded and granulated by a twin-screw extruder to obtain a masterbatch product. The extruder temperature is set at 240-280°C and the extruder speed is 300r / min-500r / min.
[0024] min, dehumidify and dry, and set aside;
[0025] (3) The components in the A, B, and C layers are mixed in proportion and dispersed evenly using a high-speed mixer;
[0026] (4) The above-mentioned uniformly mixed layers are melted and co-extruded through three extruders respectively, and the melt is cast through a T-shaped die to a chilled roller with a surface temperature of 20 to 35° C. to quench the cast sheet;
[0027] (5) placing the cast sheet in a water tank at 30 to 75° C. for 10 minutes, drying the residual moisture on the surface of the cast sheet with an air knife, and performing synchronous or distributed stretching at a stretching temperature of 130 to 190° C. and a stretching ratio of 2.5 to 3.5;
[0028] (6) The film obtained above is heat-set, and at least one of the A layer and the C layer is corona treated, and then rolled and slit to obtain the film, wherein the film thickness is 12 to 25 μm, and the A layer and the C layer are
[0029] The layer thickness is 2 to 4 μm.
[0030] The beneficial effects of the present invention are:
[0031] 1: Use organic / inorganic composite and MXD6 / PA6 composite methods to prepare high barrier films to achieve high gas barrier properties;
[0032] 2: Introducing supramolecular ionic polymers between the nano-layered structures is beneficial to the dispersion of the layers in the polyamide matrix. Combining the supramolecular ionic polymers with polyamide materials with barrier properties into thin films can effectively reduce the solubility coefficient of gas molecules in the film, form a "tortuous path" to extend the gas permeation path, and hinder the diffusion of gas in the matrix, thereby significantly improving the gas barrier properties of the polyamide film;
[0033] 3: Both the surface layer and the bottom layer are barrier layers mainly composed of MXD6, which can greatly improve the sensitivity of PA6 to water vapor and improve the barrier performance under high humidity conditions.
[0034] 4: The present invention is easy to produce and industrialize, and can greatly improve the barrier properties of the film material. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a schematic structural diagram of the high barrier biaxially stretched polyamide film of the present invention.
[0036] In the figure, A is the barrier layer, B is the core layer, and C is the barrier layer. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below in conjunction with embodiments:
[0038] The high barrier biaxially oriented polyamide film is composed of A, B, and C layers from top to bottom, and one side of the A layer is subjected to unwinding corona treatment; the A layer and the C layer are composed of PA6, MXD6, high barrier MXD6 masterbatch, and anti-sticking masterbatch; the B layer is composed of MXD6, PA6, and high barrier PA6 masterbatch.
[0039] The anti-sticking masterbatch is a modified polyamide masterbatch containing an anti-blocking agent, a lubricant and a dispersant.
[0040] High barrier MXD6 masterbatch is MXD6 modified by inorganic layered nanoparticles; high barrier PA6 masterbatch is PA6 modified by inorganic layered nanoparticles.
[0041] The inorganic layered nanoparticles are a composite of supramolecular ionomer exfoliated nanomontmorillonite (C-MMT) and supramolecular ionomer exfoliated layered double hydroxide (C-LDH).
[0042] Supramolecular ionic polymer exfoliated nanomontmorillonite (C-MMT) is an exfoliated MMT containing supramolecular ionic polymers composed of melamine cations, multifunctional imidazole cations and heteropolyacid anions between the layers.
[0043] Supramolecular ionic polymer exfoliated layered double hydroxide (C-LDH) is an exfoliated LDH composed of supramolecular ionic polymers containing sulfonic acid anions, diimidazole cations and heteropolyacid anions between the layers.
[0044] The weight ratio of supramolecular ionic polymer exfoliated nano-montmorillonite (C-MMT) to supramolecular ionic polymer exfoliated layered double hydroxide (C-LDH) is 4 / 1 to 1 / 2, and the total content of supramolecular ionic polymer exfoliated nano-montmorillonite (C-MMT) and supramolecular ionic polymer exfoliated layered double hydroxide (C-LDH) in the high barrier PA6 masterbatch is 20wt% to 30wt%;
[0045] The total content of supramolecular ionic polymer exfoliated nano-montmorillonite (C-MMT) and supramolecular ionic polymer exfoliated layered double hydroxide (C-LDH) in the high barrier MXD6 masterbatch is 30wt% to 40wt%.
[0046] Example 1
[0047] The high barrier biaxially oriented polyamide film is composed of A, B, and C layers from top to bottom, and one side of the A layer is subjected to unwinding corona treatment; the A layer and the C layer are composed of 10wt% PA6, 83.5wt% MXD6, 6wt% high barrier MXD6 masterbatch, and 0.5wt% anti-sticking masterbatch; the B layer is composed of 10wt% MXD6, 85wt% PA6, and 5wt% high barrier PA6 masterbatch;
[0048] Preparation of high barrier MXD6 masterbatch: Supramolecular ionic polymer exfoliated nano-montmorillonite (C-MMT), supramolecular ionic polymer exfoliated layered double hydroxide (C-LDH), MXD6, antioxidant, and hyperbranched rheological additive are mixed in proportion, added into a kneader, and stirred evenly to obtain a coarse material; the coarse material is crushed and mixed evenly with a coupling agent, and melt-extruded and granulated through a twin-screw extruder to obtain a masterbatch product, wherein the extruder temperature is set at 250° C., the extruder speed is 300 r / min, and after dehumidification and drying, it is set aside;
[0049] Preparation of high barrier PA6 masterbatch: Supramolecular ionic polymer exfoliated nano-montmorillonite (C-MMT), supramolecular ionic polymer exfoliated layered double hydroxide (C-LDH), PA6, antioxidant, and hyperbranched rheological additive are mixed in proportion, added into a kneader, and stirred evenly to obtain a coarse material; the coarse material is crushed and mixed evenly with a coupling agent, and melt-extruded and granulated through a twin-screw extruder to obtain a masterbatch product, wherein the extruder temperature is set at 240°C, the extruder speed is 300rmin, and after dehumidification and drying, it is set aside;
[0050] The components in the A, B and C layers are mixed in proportion and dispersed evenly by a high-speed stirrer; the above-mentioned evenly mixed layers are melted and co-extruded respectively by three extruders, and the melt is cast through a T-die to a chilled roller with a surface temperature of 20°C to quench the cast sheet; the cast sheet is subjected to humidity conditioning treatment in a 30°C water tank for 10 minutes, the residual surface moisture of the cast sheet after humidity conditioning is blown dry with an air knife, and synchronous or distributed stretching is performed, the stretching temperature is 130°C, and the stretching ratio is 2.5; the film obtained above is heat-set, and the A layer is corona treated, and then rolled and slit to obtain the film, wherein the film thickness is 12μm, and the thickness of the A layer and the C layer are both 2μm.
[0051] Example 2
[0052] The high barrier biaxially oriented polyamide film is composed of A, B, and C layers from top to bottom, and one side of the A layer is subjected to unwinding corona treatment; the A layer and the C layer are composed of 12wt% PA6, 79wt% MXD6, 8wt% high barrier MXD6 masterbatch, and 1wt% anti-sticking masterbatch; the B layer is composed of 12wt% MXD6, 80wt% PA6, and 8wt% high barrier PA6 masterbatch;
[0053] Preparation of high barrier MXD6 masterbatch: Supramolecular ionic polymer exfoliated nano-montmorillonite (C-MMT), supramolecular ionic polymer exfoliated layered double hydroxide (C-LDH), MXD6, antioxidant, and hyperbranched rheological additive are mixed in proportion, added into a kneader, and stirred evenly to obtain a coarse material; the coarse material is crushed and mixed evenly with a coupling agent, and melt-extruded and granulated through a twin-screw extruder to obtain a masterbatch product, wherein the extruder temperature is set at 255° C., the extruder speed is 350 r / min, and after dehumidification and drying, it is set aside;
[0054] Preparation of high barrier PA6 masterbatch: Supramolecular ionic polymer exfoliated nano-montmorillonite (C-MMT), supramolecular ionic polymer exfoliated layered double hydroxide (C-LDH), PA6, antioxidant, and hyperbranched rheological additive are mixed in proportion, added into a kneader, and stirred evenly to obtain a coarse material; the coarse material is crushed and mixed evenly with a coupling agent, and melt-extruded and granulated through a twin-screw extruder to obtain a masterbatch product, wherein the extruder temperature is set at 245°C, the extruder speed is 350r / min, and after dehumidification and drying, it is set aside;
[0055] The components in the A, B and C layers are mixed in proportion and dispersed evenly by a high-speed stirrer; the above-mentioned evenly mixed layers are melted and co-extruded respectively by three extruders, and the melt is cast through a T-die to a chilled roller with a surface temperature of 22°C to quench the cast sheet; the cast sheet is subjected to humidity conditioning treatment in a 40°C water tank for 10 minutes, the residual surface moisture of the cast sheet after humidity conditioning is blown dry with an air knife, and synchronous or distributed stretching is performed, the stretching temperature is 140°C, and the stretching ratio is 3; the film obtained above is heat-set, and the C layer is corona treated, and then rolled and slit to obtain the film, wherein the film thickness is 15μm, and the thickness of the A layer and the C layer are both 2μm.
[0056] Example 3
[0057] The high barrier biaxially oriented polyamide film is composed of A, B, and C layers from top to bottom, and one side of the A layer is subjected to unwinding corona treatment; the A layer and the C layer are composed of 14wt% PA6, 74wt% MXD6, 10wt% high barrier MXD6 masterbatch, and 2wt% anti-sticking masterbatch; the B layer is composed of 14wt% MXD6, 80wt% PA6, and 6wt% high barrier PA6 masterbatch;
[0058] Preparation of high barrier MXD6 masterbatch: Supramolecular ionic polymer exfoliated nano-montmorillonite (C-MMT), supramolecular ionic polymer exfoliated layered double hydroxide (C-LDH), MXD6, antioxidant, and hyperbranched rheological additive are mixed in proportion, added into a kneader, and stirred evenly to obtain a coarse material; the coarse material is crushed and mixed evenly with a coupling agent, and melt-extruded and granulated through a twin-screw extruder to obtain a masterbatch product, wherein the extruder temperature is set at 260° C., the extruder speed is 375 r / min, and after dehumidification and drying, it is set aside;
[0059] Preparation of high barrier PA6 masterbatch: Supramolecular ionic polymer exfoliated nano-montmorillonite (C-MMT), supramolecular ionic polymer exfoliated layered double hydroxide (C-LDH), PA6, antioxidant, and hyperbranched rheological additive are mixed in proportion, added into a kneader, and stirred evenly to obtain a coarse material; the coarse material is crushed and mixed evenly with a coupling agent, and melt-extruded and granulated through a twin-screw extruder to obtain a masterbatch product, wherein the extruder temperature is set at 250°C, the extruder speed is 375r / min, and after dehumidification and drying, it is set aside;
[0060] The components in the A, B and C layers are mixed in proportion and dispersed evenly by a high-speed stirrer; the above-mentioned evenly mixed layers are melted and co-extruded respectively by three extruders, and the melt is cast through a T-die to a chilled roller with a surface temperature of 24°C to quench the cast sheet; the cast sheet is subjected to humidity conditioning treatment in a 50°C water tank for 10 minutes, the residual surface moisture of the cast sheet after humidity conditioning is blown dry with an air knife, and synchronous or distributed stretching is performed, the stretching temperature is 150°C, and the stretching ratio is 3.5; the film obtained above is heat-set, and the A layer is corona treated, and then rolled and slit to obtain the film, wherein the film thickness is 12μm, and the thickness of the A layer and the C layer are both 2μm.
[0061] Example 4
[0062] The high barrier biaxially oriented polyamide film is composed of A, B, and C layers from top to bottom, and one side of the A layer is subjected to unwinding corona treatment; the A layer and the C layer are composed of 15wt% PA6, 70wt% MXD6, 12wt% high barrier MXD6 masterbatch, and 3wt% anti-sticking masterbatch; the B layer is composed of 16wt% MXD6, 80wt% PA6, and 6wt% high barrier PA6 masterbatch;
[0063] Preparation of high barrier MXD6 masterbatch: Supramolecular ionic polymer exfoliated nano-montmorillonite (C-MMT), supramolecular ionic polymer exfoliated layered double hydroxide (C-LDH), MXD6, antioxidant, and hyperbranched rheological additive are mixed in proportion, added into a kneader, and stirred evenly to obtain a coarse material; the coarse material is crushed and mixed evenly with a coupling agent, and melt-extruded and granulated through a twin-screw extruder to obtain a masterbatch product, wherein the extruder temperature is set at 265° C., the extruder speed is 400 r / min, and after dehumidification and drying, it is set aside;
[0064] Preparation of high barrier PA6 masterbatch: Supramolecular ionic polymer exfoliated nano-montmorillonite (C-MMT), supramolecular ionic polymer exfoliated layered double hydroxide (C-LDH), PA6, antioxidant, and hyperbranched rheological additive are mixed in proportion, added into a kneader, and stirred evenly to obtain a coarse material; the coarse material is crushed and mixed evenly with a coupling agent, and melt-extruded and granulated through a twin-screw extruder to obtain a masterbatch product, wherein the extruder temperature is set at 255°C, the extruder speed is 400r / min, and after dehumidification and drying, it is set aside;
[0065] The components in the A, B and C layers are mixed in proportion and dispersed evenly by a high-speed stirrer; the above-mentioned evenly mixed layers are melted and co-extruded respectively by three extruders, and the melt is cast through a T-die to a chilled roller with a surface temperature of 25°C to quench the cast sheet; the cast sheet is subjected to humidity conditioning treatment in a 60°C water tank for 10 minutes, the residual surface moisture of the cast sheet after humidity conditioning is blown dry with an air knife, and synchronous or distributed stretching is performed, the stretching temperature is 160°C, and the stretching ratio is 4; the film obtained above is heat-set, and the A layer is corona treated, and then rolled and slit to obtain the film, wherein the film thickness is 15μm, and the thickness of the A layer and the C layer are both 2μm.
[0066] Example 5
[0067] The high barrier biaxially oriented polyamide film is composed of A, B, and C layers from top to bottom, and one side of the A layer is subjected to unwinding corona treatment; the A layer and the C layer are composed of 16wt% PA6, 68wt% MXD6, 14wt% high barrier MXD6 masterbatch, and 2wt% anti-sticking masterbatch; the B layer is composed of 18wt% MXD6, 80wt% PA6, and 2wt% high barrier PA6 masterbatch;
[0068] Preparation of high barrier MXD6 masterbatch: Supramolecular ionic polymer exfoliated nano-montmorillonite (C-MMT), supramolecular ionic polymer exfoliated layered double hydroxide (C-LDH), MXD6, antioxidant, and hyperbranched rheological additive are mixed in proportion, added into a kneader, and stirred evenly to obtain a coarse material; the coarse material is crushed and mixed evenly with a coupling agent, and melt-extruded and granulated through a twin-screw extruder to obtain a masterbatch product, wherein the extruder temperature is set at 270°C, the extruder speed is 425r / min, and after dehumidification and drying, it is set aside;
[0069] Preparation of high barrier PA6 masterbatch: Supramolecular ionic polymer exfoliated nano-montmorillonite (C-MMT), supramolecular ionic polymer exfoliated layered double hydroxide (C-LDH), PA6, antioxidant, and hyperbranched rheological additive are mixed in proportion, added into a kneader, and stirred evenly to obtain a coarse material; the coarse material is crushed and mixed evenly with a coupling agent, and melt-extruded and granulated through a twin-screw extruder to obtain a masterbatch product, wherein the extruder temperature is set at 260°C, the extruder speed is 425r / min, and after dehumidification and drying, it is set aside;
[0070] The components in the A, B and C layers are mixed in proportion and dispersed evenly by a high-speed stirrer; the above-mentioned evenly mixed layers are melted and co-extruded respectively by three extruders, and the melt is cast through a T-die to a chilled roller with a surface temperature of 26°C to quench the cast sheet; the cast sheet is subjected to humidity conditioning treatment in a 70°C water tank for 10 minutes, the residual surface moisture of the cast sheet after humidity conditioning is blown dry with an air knife, and synchronous or distributed stretching is performed, the stretching temperature is 180°C, and the stretching ratio is 3.5; the film obtained above is heat-set, and the C layer is corona treated, and then rolled and slit to obtain the film, wherein the film thickness is 25μm, and the thickness of the A layer and the C layer are both 4μm.
[0071] Example 6
[0072] The high barrier biaxially oriented polyamide film is composed of A, B, and C layers from top to bottom, and one side of the A layer is subjected to unwinding corona treatment; the A layer and the C layer are composed of 18wt% PA6, 66wt% MXD6, 15wt% high barrier MXD6 masterbatch, and 1wt% anti-sticking masterbatch; the B layer is composed of 20wt% MXD6, 72wt% PA6, and 8wt% high barrier PA6 masterbatch;
[0073] Preparation of high barrier MXD6 masterbatch: Supramolecular ionic polymer exfoliated nano-montmorillonite (C-MMT), supramolecular ionic polymer exfoliated layered double hydroxide (C-LDH), MXD6, antioxidant, and hyperbranched rheological additive are mixed in proportion, added into a kneader, and stirred evenly to obtain a coarse material; the coarse material is crushed and mixed evenly with a coupling agent, and melt-extruded and granulated through a twin-screw extruder to obtain a masterbatch product, wherein the extruder temperature is set at 280°C, the extruder speed is 450r / min, and after dehumidification and drying, it is set aside;
[0074] Preparation of high barrier PA6 masterbatch: Supramolecular ionic polymer exfoliated nano-montmorillonite (C-MMT), supramolecular ionic polymer exfoliated layered double hydroxide (C-LDH), PA6, antioxidant, and hyperbranched rheological additive are mixed in proportion, added into a kneader, and stirred evenly to obtain a coarse material; the coarse material is crushed and mixed evenly with a coupling agent, and melt-extruded and granulated through a twin-screw extruder to obtain a masterbatch product, wherein the extruder temperature is set at 270°C, the extruder speed is 450r / min, and after dehumidification and drying, it is set aside;
[0075] The components in the A, B and C layers are mixed in proportion and dispersed evenly by a high-speed stirrer; the above-mentioned evenly mixed layers are melted and co-extruded respectively by three extruders, and the melt is cast through a T-die to a chilled roller with a surface temperature of 28°C to quench the cast sheet; the cast sheet is subjected to humidity conditioning treatment in a 75°C water tank for 10 minutes, the residual surface moisture of the cast sheet after humidity conditioning is blown dry with an air knife, and synchronous or distributed stretching is performed, the stretching temperature is 190°C, and the stretching ratio is 3; the film obtained above is heat-set, and the A layer is corona treated, and then rolled and slit to obtain the film, wherein the film thickness is 25μm, and the thickness of the A layer and the C layer are both 4μm.
[0076] Example 7
[0077] The high barrier biaxially oriented polyamide film is composed of A, B, and C layers from top to bottom, and one side of the A layer is subjected to unwinding corona treatment; the A layer and the C layer are composed of 20wt% PA6, 67.5wt% MXD6, 12wt% high barrier MXD6 masterbatch, and 0.5wt% anti-sticking masterbatch; the B layer is composed of 12wt% MXD6, 84wt% PA6, and 4wt% high barrier PA6 masterbatch;
[0078] Preparation of high barrier MXD6 masterbatch: Supramolecular ionic polymer exfoliated nano-montmorillonite (C-MMT), supramolecular ionic polymer exfoliated layered double hydroxide (C-LDH), MXD6, antioxidant, and hyperbranched rheological additive are mixed in proportion, added into a kneader, and stirred evenly to obtain a coarse material; the coarse material is crushed and mixed evenly with a coupling agent, and melt-extruded and granulated through a twin-screw extruder to obtain a masterbatch product, wherein the extruder temperature is set at 285° C., the extruder speed is 475 r / min, and after dehumidification and drying, it is set aside;
[0079] Preparation of high barrier PA6 masterbatch: Supramolecular ionic polymer exfoliated nano-montmorillonite (C-MMT), supramolecular ionic polymer exfoliated layered double hydroxide (C-LDH), PA6, antioxidant, and hyperbranched rheological additive are mixed in proportion, added into a kneader, and stirred evenly to obtain a coarse material; the coarse material is crushed and mixed evenly with a coupling agent, and melt-extruded and granulated through a twin-screw extruder to obtain a masterbatch product, wherein the extruder temperature is set at 275°C, the extruder speed is 475r / min, and after dehumidification and drying, it is set aside;
[0080] The components in the A, B and C layers are mixed in proportion and dispersed evenly by a high-speed stirrer; the above-mentioned evenly mixed layers are melted and co-extruded respectively by three extruders, and the melt is cast through a T-die to a chilled roller with a surface temperature of 30°C to quench the cast sheet; the cast sheet is subjected to humidity conditioning treatment in a 60°C water tank for 10 minutes, the residual surface moisture of the cast sheet after humidity conditioning is blown dry with an air knife, and synchronous or distributed stretching is performed, the stretching temperature is 140°C, and the stretching ratio is 2.5; the film obtained above is heat-set, and the C layer is corona treated, and then rolled and slit to obtain the film, wherein the film thickness is 20μm, and the thickness of the A layer and the C layer are both 3μm.
[0081] Example 8
[0082] The high barrier biaxially oriented polyamide film is composed of A, B, and C layers from top to bottom, and one side of the A layer is subjected to unwinding corona treatment; the A layer and the C layer are composed of 10wt% PA6, 81wt% MXD6, 8wt% high barrier MXD6 masterbatch, and 1wt% anti-sticking masterbatch; the B layer is composed of 10wt% MXD6, 82wt% PA6, and 8wt% high barrier PA6 masterbatch;
[0083] Preparation of high barrier MXD6 masterbatch: Supramolecular ionic polymer exfoliated nano-montmorillonite (C-MMT), supramolecular ionic polymer exfoliated layered double hydroxide (C-LDH), MXD6, antioxidant, and hyperbranched rheological additive are mixed in proportion, added into a kneader, and stirred evenly to obtain a coarse material; the coarse material is crushed and mixed evenly with a coupling agent, and melt-extruded and granulated through a twin-screw extruder to obtain a masterbatch product, wherein the extruder temperature is set at 290° C., the extruder speed is 500 r / min, and after dehumidification and drying, it is set aside;
[0084] Preparation of high barrier PA6 masterbatch: Supramolecular ionic polymer exfoliated nano-montmorillonite (C-MMT), supramolecular ionic polymer exfoliated layered double hydroxide (C-LDH), PA6, antioxidant, and hyperbranched rheological additive are mixed in proportion, added into a kneader, and stirred evenly to obtain a coarse material; the coarse material is crushed and mixed evenly with a coupling agent, and melt-extruded and granulated through a twin-screw extruder to obtain a masterbatch product, wherein the extruder temperature is set at 280°C, the extruder speed is 500r / min, and after dehumidification and drying, it is set aside;
[0085] The components in the A, B and C layers are mixed in proportion and dispersed evenly by a high-speed stirrer; the above-mentioned evenly mixed layers are melted and co-extruded respectively by three extruders, and the melt is cast through a T-die to a chilled roller with a surface temperature of 35°C to quench the cast sheet; the cast sheet is subjected to humidity conditioning treatment in a 50°C water tank for 10 minutes, the residual surface moisture of the cast sheet after humidity conditioning is blown dry with an air knife, and synchronous or distributed stretching is performed, the stretching temperature is 130°C, and the stretching ratio is 2.5; the film obtained above is heat-set, and the C layer is corona treated, and then rolled and slit to obtain the film, wherein the film thickness is 20μm, and the thickness of the A layer and the C layer are both 3μm.
[0086] The high barrier biaxially oriented polyamide films prepared in the above embodiments were tested, and the measured properties were as follows:
[0087] Table 1. Performance comparison of various embodiments
[0088]
Claims
1. A high barrier biaxially oriented polyamide film, characterized in that: It consists of three layers of co-extruded biaxially oriented polyamide film, A, B, and C, from top to bottom; Layer A and layer C are composed of 10wt% to 20wt% PA6, 66wt% to 83.5XD6, 6wt% to 15 high barrier MXD 6 masterbatch, and 0.5wt% to 3wt% anti-sticking masterbatch; The B layer is composed of 10wt% to 20wt% of MXD6, 70wt% to 85wt% of PA6, and 2wt% to 8wt% of high barrier PA6 masterbatch.
2. The high barrier biaxially oriented polyamide film according to claim 1, characterized in that: The thickness of the high barrier biaxially oriented polyamide film is 12-25 μm, the thickness of the A layer and the C layer are both 2-4 μm, and at least one side of the A layer and the C layer is subjected to corona treatment.
3. The high barrier biaxially oriented polyamide film according to claim 1, characterized in that: The anti-sticking masterbatch is a modified polyamide masterbatch containing an anti-blocking agent, a lubricant and a dispersant.
4. The high barrier biaxially oriented polyamide film according to claim 1, characterized in that: High barrier MXD6 masterbatch is MXD6 modified by inorganic layered nanoparticles; high barrier PA6 masterbatch is PA6 modified by inorganic layered nanoparticles.
5. The high barrier biaxially oriented polyamide film according to claim 4, characterized in that: The inorganic layered nanoparticles are a composite of supramolecular ion polymer exfoliated nano-montmorillonite and supramolecular ion polymer exfoliated layered double hydroxide.
6. The high barrier biaxially oriented polyamide film according to claim 5, characterized in that: The supramolecular ionic polymer exfoliated nano-montmorillonite is an exfoliated MMT containing supramolecular ionic polymers composed of melamine cations, multifunctional imidazole cations and heteropolyacid anions between the layers.
7. The high barrier biaxially oriented polyamide film according to claim 6, characterized in that: The supramolecular ionic polymer exfoliated layered double hydroxide is an exfoliated LDH composed of supramolecular ionic polymers containing sulfonic acid anions, diimidazole cations and heteropolyacid anions between the layers.
8. The high barrier biaxially oriented polyamide film according to claim 7, characterized in that: The weight ratio of supramolecular ionic polymer stripped nano-montmorillonite to supramolecular ionic polymer stripped layered double hydroxide is 4 / 1-1 / 2, and the total content of supramolecular ionic polymer stripped nano-montmorillonite and supramolecular ionic polymer stripped layered double hydroxide in the high barrier PA6 masterbatch is 20wt%-30wt%.
9. The high barrier biaxially oriented polyamide film according to claim 7, characterized in that: The weight ratio of supramolecular ion polymer stripped nano-montmorillonite to supramolecular ion polymer stripped layered double hydroxide is 4 / 1-1 / 2, and the total content of supramolecular ion polymer stripped nano-montmorillonite and supramolecular ion polymer stripped layered double hydroxide in the high barrier MXD6 masterbatch is 30wt%-40wt%.
10. A high barrier biaxially oriented polyamide film and a preparation method thereof according to claim 1, characterized in that The following steps are involved: (1) Preparation of high barrier MXD6 masterbatch: Supramolecular ion polymer exfoliated nano-montmorillonite, supramolecular ion polymer exfoliated layered double hydroxide, MXD6, antioxidant, and hyperbranched rheological additive are mixed in proportion, added into a kneader, and stirred evenly to obtain a coarse material; The coarse material is crushed and mixed with the coupling agent, and then melt-extruded and granulated by a twin-screw extruder to obtain a masterbatch product, wherein the extruder temperature is set at 250-290°C and the extruder speed is 300r / min-500r / min. min, dehumidify and dry, and set aside; (2) Preparation of high barrier PA6 masterbatch: Supramolecular ion polymer exfoliated nano-montmorillonite, supramolecular ion polymer exfoliated layered double hydroxide, PA6, antioxidant, and hyperbranched rheological additive are mixed in proportion, added into a kneader, and stirred evenly to obtain a coarse material; The coarse material is crushed and mixed with the coupling agent, and then melt-extruded and granulated by a twin-screw extruder to obtain a masterbatch product. The extruder temperature is set at 240-280°C and the extruder speed is 300r / min-500r / min. min, dehumidify and dry, and set aside; (3) The components in the A, B, and C layers are mixed in proportion and dispersed evenly using a high-speed mixer; (4) The above-mentioned uniformly mixed layers are melted and co-extruded through three extruders respectively, and the melt is cast through a T-shaped die to a chilled roller with a surface temperature of 20 to 35° C. to quench the cast sheet; (5) placing the cast sheet in a water tank at 30 to 75° C. for 10 minutes, drying the residual moisture on the surface of the cast sheet with an air knife, and performing synchronous or distributed stretching at a stretching temperature of 130 to 190° C. and a stretching ratio of 2.5 to 3.5; (6) The film obtained above is heat-set, and at least one of the A layer and the C layer is corona treated, and then rolled and slit to obtain the film, wherein the film thickness is 12 to 25 μm, and the thickness of the A layer and the C layer are both 2 to 4 μm.
Citation Information
Patent Citations
Photo-cured acrylate-layered double hydroxide nano composite material and preparation method thereof
CN101555304A
High-barrier nylon film and preparation method thereof
CN102794968A
Preparation method and application of secondary modified layered double hydroxide
CN103965661A
High-barrier scratch-resistant biaxially oriented polyamide film and preparation method thereof
CN110641118A
Containers having improved barrier and mechanical properties
US6841211B1